Molecular Profiling in Thyroid cancer- Using next generation sequencing to differentiate rare cases of papillary thyroid hyperplasia from papillary thyroid carcinoma. (28th October 2021) - Lazim, A; Luceno, S; Arriola, A; Seth, A; Jhala, N
Abstract: Introduction/Objective: Differentiating papillary thyroid hyperplasia from papillary thyroid carcinoma is made primarily on differences in key histologic and cytomorphologic features. These include architectural features such as invasion and nuclear changes such as chromatin pallor, nuclear grooves, and intranuclear pseudoinclusions. Distinguishing between these two diagnoses is not always straightforward in a minority of cases, as papillary thyroid hyperplasia nodules can be misinterpreted as papillary thyroid carcinoma and vice versa. This is because the nuclear changes can be subtle and be induced artificially by poor or inadequate formalin fixation. Immunostains such as cytokeratin 19 (CK19), galectin-3, and HBME1 may be used to distinguish between papillary thyroid hyperplastic nodules and papillary thyroid carcinoma; however, as immunostaining results are not always definitive, other more definitive ancillary tests are sometimes utilized such as molecular testing. Methods/Case Report: Thyroid cases with indeterminate diagnoses (n=6) were obtained from the archives. Such cases included papillary thyroid hyperplasia and cases with descriptive diagnoses such as well-differentiated encapsulated and low-grade papillary carcinoma. Five cases of definitive papillary thyroid carcinoma and one case of follicular thyroid carcinoma (n=6) were used as a comparison group. Next generation sequencing (NGS) assays were performed using a custom SLIMamp targeted DNA solid tumor panel (Pillar Biosciences) and a targeted multi gene RNA fusion panel (Invitae). Results (if a Case Study enter NA): All of the definitive cases of papillary thyroid carcinoma showed characteristic mutations such as BRAF V600E as well as RNA fusions such as RET/PTC while all of the indeterminate cases did not show any detectable DNA mutations or RNA fusions, confirming their benign nature. A separate case that was signed out as non-invasive follicular thyroid neoplasm with papillary-like nuclear features showed an NRAS Q61R mutation and a novel ETV1-ERG fusion. Conclusion: This study demonstrates the utility of molecular testing as an adjunct to histopathological evaluation in definitive diagnosis and differentiation of papillary thyroid hyperplasia from papillary carcinoma. Next generation sequencing with targeted DNA and RNA panels will be beneficial for both known and novel variant or fusion detection in suspect cases.